How to optimize exercise behavior in axial spondyloarthritis? Results of an intervention mapping study. Issue 5 (May 2020) - Hilberdink, Bas; van der Giesen, Florus; Vliet Vlieland, Thea; Nijkamp, Marjan; van Weely, Salima
Highlights: Only a third of axSpA patients exercise frequently, despite proven health benefits. Eight relevant determinants of axSpA patients´ exercise behavior were identified. Ten intervention components were selected to target the identified determinants. An intervention with behavior change guidance and therapists´ training is proposed. Abstract: Objective: Many individuals with axial spondyloarthritis (axSpA) do not engage in adequate exercise, despite its proven health benefits. This study aimed to identify the intervention components needed to optimize exercise behavior in people with axSpA. Methods: The first three steps of the Intervention Mapping protocol were used: 1) needs assessment; 2) identification of axSpA-specific exercise barriers and facilitators (´determinants'); 3) selection of effective intervention components addressing potentially modifiable determinants. All three steps included scoping reviews and semi-structured interviews with patients (n = 2) and physical therapists (n = 2). Results: The scoping reviews included 28, 23 and 15 papers, respectively. Step 1 showed that only one third of axSpA patients exercise regularly, demonstrating especially a lack of strengthening and cardiorespiratory exercises. Based on eight determinants identified in Step 2, 10 intervention components were selected in Step 3: education, motivational interviewing, goal setting, action planning, monitoring, feedback, tailoring, guided practice, therapists' training and group exercise encouragement. Conclusion: Using the Intervention Mapping method, 10 intervention components for optimizing exercise behavior in people with axSpA were identified and an intervention with behavior change guidance and a training for health professionals is proposed. Practice Implications: This study provides a foundation for the development of an axSpA-specific exercise intervention.